Elastisitas Kesempatan Kerja Sektoral di Kabupaten/Kota Provinsi Bali - Lestari, Ni Wayan Yuni; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 12, Desember 2016 (pp. 1347-1585), 2017)
The goal of national development is to improve economic performance in order to able to create work opportunity and absorb many labour. Elasticity of work opportunity give overview about comparation between work opportuntiy growth procentage with procentage of bruto regional domestic product growth. Elasticity of high opportunity reflection of work opportunity which can be absorbed also high. This study aims 1) to analyze  condition of elasticity of work oppotunity at regional of Bali province, 2)  to analyize development of work opportunity at regency/city in Bali province, 3) to analyze difference of work opportunity elasticity in development regional of Bali province, 4) to analyze difference of work opportunity according regency/city sectoral in Bali province. Location of this study was conducted at Bali province divided into eight regency and one city by using data of time series during 10 years at regency/city so that total data is 90. This study by using data collection with observation method. Data was analyzed by using descriptive statistic and analysis of varians. The result shows as follows 1) elasticity condition of work opportunity at Bali province have vary according regency/city 2) development of work opportunity elasticity at  each regency/city at Bali province tend fluctuation 3) elasticity of work opportunity dont difference signfiicant accordding sector it meaning ability from third sectors not different sigificant relatively/procentage, 4) there is difference significant work opportunity according sector at Bali province. Based on the result suggested  investment can be directed at sector that  have lower work opportunity absorb.
Keywords: Elasticity,work opportunity,sector,development region